Role-based collaborative task planning of heterogeneous multi-autonomous underwater vehicles. (25th June 2019) - Zhang, Lanyong; Zhang, Lei; Liu, Sheng
The multi-autonomous underwater vehicles (Multi-AUVs) cluster is an important means to solve the marine tasks effectively. The heterogeneous Multi-AUVs are constrained by cooperative relationship, and a model of multi-autonomous underwater vehicles role-based collaborative task planning is proposed. The Multi-AUVs are set to different roles depending on the functional properties. To analyze the accountability of each role, and to ensure the reliability, the desired behavior and the estimate state of each role are described in the model. Task allocation needs to be implemented dynamically in path planning, for the existing of the cooperative relationships and the demand of tasks changes. Role-based task assessment and allocation methods are proposed to achieve dynamic adjustment of roles according to task requirements. Due to poor underwater communication conditions, the implicit coordination framework is implied to the coordinate information interaction to compensate the large delays in underwater communications and the reliance between Multi-AUVs. To adapt to the implicit collaborative framework and poor communication conditions, a variable communication radius (contract network) is proposed. The simulation result shows that the proposed method has well performance.